2021
DOI: 10.1557/s43578-021-00322-2
|View full text |Cite
|
Sign up to set email alerts
|

Stiff and strong, lightweight bi-material sandwich plate-lattices with enhanced energy absorption

Abstract: Plate-based lattices are predicted to reach theoretical Hashin-Shtrikman and Suquet upper bounds on stiffness and strength. However, simultaneously attaining high energy absorption in these plate-lattices still remains elusive, which is critical for many structural applications such as shock wave absorber and protective devices. In this work, we present bi-material isotropic cubic + octet sandwich plate-lattices composed of carbon fiber-reinforced polymer (stiff) skins and elastomeric (soft) core. This bi-mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Recently, the utilization of biphasic/multimaterial composition was exploited to enhance the energy absorption of plate lattice materials. Meng‐Ting Hsieh et al [ 131 ] designed a biphasic SC‐FCC plate lattice composed of an elastomeric soft core sandwiched between two carbon fiber‐reinforced polymer (CFRP) plies, where the weight fraction of the soft core ( V soft ) was varied from 0% to 50%. Numerical analysis demonstrated that increasing the V soft from 0% (i.e., a sample completely made of CFRP) to 27.5% enhanced the energy absorption of the biphasic design by 250% (in average).…”
Section: Design and Performance Optimizationmentioning
confidence: 99%
“…Recently, the utilization of biphasic/multimaterial composition was exploited to enhance the energy absorption of plate lattice materials. Meng‐Ting Hsieh et al [ 131 ] designed a biphasic SC‐FCC plate lattice composed of an elastomeric soft core sandwiched between two carbon fiber‐reinforced polymer (CFRP) plies, where the weight fraction of the soft core ( V soft ) was varied from 0% to 50%. Numerical analysis demonstrated that increasing the V soft from 0% (i.e., a sample completely made of CFRP) to 27.5% enhanced the energy absorption of the biphasic design by 250% (in average).…”
Section: Design and Performance Optimizationmentioning
confidence: 99%
“…Here we demonstrate a new class of ultralow density elastic micro-architected metamaterials with starshaped re-entrant topologies that can achieve wide-band omnidirectional vibration attenuation. The high porosity (exceeding 90% void space) of the proposed micro-lattice enables low mass density as low as 0.09 g/cm 3 . The design features a network of low stiffness suspended nodal structures within overhanging micro-unit cells that facilitate a Fig.…”
Section: Ultralight Elastic Metamaterialsmentioning
confidence: 99%
“…Architected metamaterials with designed three-dimensional architectures exhibit extraordinary structural and multi-functional properties that are not observed in nature and are attractive candidates for applications in energy absorption [1][2][3], energy transduction [4], fluid control [5], electronic sensors [6,7], and sound management [8,9]. While advances in additive manufacturing (AM) techniques, capable of complex and high-resolution features, have made the realization of some of these concepts possible [10][11][12], most additively manufacturable designs are limited to self-supported 3D architectures that exhibit structurally rigid properties.…”
Section: Introductionmentioning
confidence: 99%
“…Another emerging category of micro-architected structure are plate-based lattices, due to their potential to achieve the upper bounds for isotropic elasticity and strain energy storage (i.e., the Hashin-Shtrikman upper bounds) [59]. However, its superior mechanical property comes at the cost of the manufacturing feasibility, as their closedcell nature obstacles the use of powder-bed AM technique.…”
Section: Plate-based Structuresmentioning
confidence: 99%